Limit States of Shallow Bridge Foundations With Sheet Piling Covers - Michał Wymysłowski (The Baltic Journal of Road and Bridge Engineering)
This article presents an analytical method which takes into account the beneficial effects of the sheet piling located around the foundation in the calculations of ULS and SLS of shallow foundations. The analytical method proposed by the author was described in detail on the example of a “theoretical bridge” with the assumed geometry and loads as well as with the assumed subsoil and water conditions under the bridge. The stresses in the subsoil under the foundation and the settlement were determined. The author’s method was also used to calculate the foundation settlement of an “existing bridge” located in Gdańsk (Poland). In both cases, the results were compared with the results obtained using PLAXIS 3D Advanced 2023.1 and additionally with geodetic measurements for “existing bridge”. The author’s proposal was based on the EN 1997-1: Eurocode 7 standard applicable in the European Union. It has original elements that are not included in the cited standard. The proposed method is not the only one that could be used to assess the limit states of shallow foundations with sheet piling cover. However, it is based on the applicable regulations, gives similar results to the results obtained with FEM and geodetic measurements.